Biological Activities of Phenolics from the Fruits of Phyllanthus emblica L. (Euphorbiaceae) - Jie Zhang (2018)
© 2017 Wiley-VHCA AG, Zurich, Switzerland Seven phenolic compounds, 1 – 7, including a new organic acid gallate, mucic acid 1-ethyl 6-methyl ester 2-O-gallate (7), were isolated from the MeOH extract of the fruits of Phyllanthus emblica L. (Euphorbiaceae). The structures were elucidated on the basis of extensive spectroscopic analysis and comparison with literature data. Upon evaluated for their antioxidant abilities by 1,1-diphenyl-2-picrylhydrazyl (DPPH), 2,2′-azinobis(3-ethylbenzthiazoline-6-sulfonic acid) (ABTS), and ferric reducing antioxidant power (FRAP) assays. The inhibitory activities against melanogenesis in B16 melanoma cells induced by α-MSH, as well as cytotoxic activities against four human cancer cell lines were also evaluated. All phenolic compounds, 1 – 7, exhibited potent antioxidant abilities (DPPH: IC505.6 – 12.9 μm; ABTS: 0.87 – 8.43 μm Trolox/μm; FRAP: 1.01 – 5.79 μm Fe2+/μm, respectively). Besides, 5 – 7, also exhibited moderate inhibitory activities against melanogenesis (80.7 – 86.8% melanin content), even with no or low toxicity to the cells (93.5 – 101.6% cell viability) at a high concentration of 100 μm. Compounds 1 – 3 exhibited cytotoxic activity against one or more cell lines (IC5013.9 – 68.4%), and compound 1 with high tumor selectivity for A549 (SI 3.2).